Contribution of Flipped Classroom Model on University Students’ Writing Performance, Writing Self-Efficacy, and Writing Self- Regulation - Helaluddin, Helaluddin; Ismail, Gunawan `; Awalludin, Awalludin (Jurnal Pendidikan Progresif, 2024)
Contribution of Flipped Classroom Model on University Students’ Writing Performance, Writing Self-Efficacy, and Writing Self-Regulation. Objectives: After the pandemic ended, education experts recommended the flipped classroom model as an alternative learning model teachers could use. This model combines class activities and at home to make learning more effective and efficient. This study aims to explore the impact of the flipped classroom model on improving writing performance, writing self-efficacy, and writing self-regulation for students. Methods: The researcher used a quasi-experimental pretest-posttest design involving 58 students in the Islamic Economics Study Program, UIN Sultan Maulana Hasanuddin Banten, Indonesia. Data was collected using four main instruments: writing tests, writing performance assessment rubrics, writing self-efficacy questionnaires, and writing self-regulation questionnaires. Researchers ran a paired sample t-test and one-way ANCOVA to analyze the data. Findings: The results showed that the flipped classroom model positively affected students’ writing performance, writing self-efficacy, and writing self-regulation. Conclusion: Based on these findings, the researchers recommend that teachers use the flipped classroom model in teaching academic writing, especially in dealing with learning in the post-pandemic era. Keywords: flipped classroom, writing performance, writing self-efficacy, and writing self-regulation.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024107